2020
DOI: 10.3390/antibiotics9110820
|View full text |Cite
|
Sign up to set email alerts
|

Extended Spectrum Beta-Lactamase-Resistant Determinants among Carbapenem-Resistant Enterobacteriaceae from Beef Cattle in the North West Province, South Africa: A Critical Assessment of Their Possible Public Health Implications

Abstract: Carbapenems are considered to be the last resort antibiotics for the treatment of infections caused by extended-spectrum beta-lactamase (ESBL)-producing strains. The purpose of this study was to assess antimicrobial resistance profile of Carbapenem-resistant Enterobacteriaceae (CRE) isolated from cattle faeces and determine the presence of carbapenemase and ESBL encoding genes. A total of 233 faecal samples were collected from cattle and analysed for the presence of CRE. The CRE isolates revealed resistance ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 50 publications
(54 reference statements)
0
11
1
Order By: Relevance
“…The beta-lactamase enzyme (bla TEM ) was firstly identified in K. pneumoniae and Gram-negative bacteria (Tshitshi et al, 2020). Mutation of TEM genes could occur if a single amino acid or multiplier were substituted around the active site of its enzyme (Dantas and Ferreira, 2020) The mobile genetic elements (MGE) could transfer the resistant genes in beta-lactamase-producing enzymes bacteria (Eka and Pinatih, 2017).…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%
“…The beta-lactamase enzyme (bla TEM ) was firstly identified in K. pneumoniae and Gram-negative bacteria (Tshitshi et al, 2020). Mutation of TEM genes could occur if a single amino acid or multiplier were substituted around the active site of its enzyme (Dantas and Ferreira, 2020) The mobile genetic elements (MGE) could transfer the resistant genes in beta-lactamase-producing enzymes bacteria (Eka and Pinatih, 2017).…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%
“…To date, antibiotic therapy is still regarded as an essential treatment of secondary infections [ 39 ], despite the rise in microbial resistance, hence the evolution of chronic diseases [ 40 , 41 ]. A number of studies have reported antimicrobial properties such as antibacterial, antifungal and antiviral properties of the genera Drimia in both in vitro and in vivo models.…”
Section: Biological Activities Of Drimia Sppmentioning
confidence: 99%
“…The antimicrobial resistance profiles of the isolates were determined by the disc diffusion assay on Mueller Hinton agar following the CLSI (Clinical Laboratory Standards Institute) recommendations [50]. Twelve antibiotics (Mast Diagnostics, UK) belonging to seven groups were used: β-lactam/ β-lactamase inhibitor (Piperacillin-tazobactam, 100 μg /10 μg), Carbapenem (Meropenem, 10 μg), Monobactam (Aztreonam, 30 μg), Aminoglycoside (Gentamicin, 10 μg; Amikacin, 30 μg), Quinolone (Ciprofloxacin), Cephem (Cefepime, 30 μg; Cefotaxime, 30 μg; Ceftriaxone, 30 μg; Cefuroxime, 30 μg and Ceftazidime, 30 μg) and folate pathway inhibitor (Trimethoprim-Sulfamethoxazole, 1.25/ 23.75 μg).…”
Section: Antimicrobial Susceptibility Testingmentioning
confidence: 99%
“…Twelve antibiotics (Mast Diagnostics, UK) belonging to seven groups were used: β-lactam/ β-lactamase inhibitor (Piperacillin-tazobactam, 100 μg /10 μg), Carbapenem (Meropenem, 10 μg), Monobactam (Aztreonam, 30 μg), Aminoglycoside (Gentamicin, 10 μg; Amikacin, 30 μg), Quinolone (Ciprofloxacin), Cephem (Cefepime, 30 μg; Cefotaxime, 30 μg; Ceftriaxone, 30 μg; Cefuroxime, 30 μg and Ceftazidime, 30 μg) and folate pathway inhibitor (Trimethoprim-Sulfamethoxazole, 1.25/ 23.75 μg). These antimicrobial agents were selected based on resistance data from some previous studies conducted in the study area [15,50]. In addition, third-generation cephalosporins were included in the evaluation due to the fact that they have a wide activity against gram-negative microorganisms and are very useful for the treatment of serious bacterial infections in humans.…”
Section: Antimicrobial Susceptibility Testingmentioning
confidence: 99%